ВТРАТИ ЕНЕРГІЇ В БАГАТОКОМІРКОВИХ ТРАНЗИСТОРНИХ ПЕРЕТВОРЮВАЧАХ ДЛЯ КОНТАКТНОГО ЗВАРЮВАННЯ - Бондаренко, О.Ф.; Хижняк, Т.А.; Кузін , Д.В. (Інститут електродинаміки НАН України, Київ, 2015)
The analysis of energy loss components in multicell-type transistor converters for resistance welding with continuous control, pulse control and combined pulse and continuous control were carried out. The formulas for calculating energy losses in converters and their efficiency, considering the losses in energy storage and welding current control unit, were obtained. The calculations using obtained formulas were carried out. The calculation results showed that the efficiency of the converter with combined pulse and continuous control is higher than the efficiency of the converter with the continuous control at specified voltage values of energy storage, and the smaller this voltage, the closer the efficiency of the converter with combined control to the efficiency of converter with pulse control. References 9, tables 1, figures 4